How we exchange glances with images: The Image as the Matter of the Body - Belting, Hans (Iluminace, 2009)
The author asks the question whether we look at images or whether images are only realised in our gaze. Is the image a traditional object of observation or is it rather an act of our body? The author develops a theory of the trinity of image, medium and body. Visual culture is then not a collection of artifacts, but rather a sequence of repeating and changing events.
Keywords: film theory; image analysis; perception; identification; psychology; film aesthetics